Service Quality and Customer Loyalty at Grapari - Arhas, Sitti Hardiyanti; Suprianto, Suprianto; Darwis, Muhammad; Saleh, Sirajuddin; Jamaluddin, Jamaluddin; Nasrullah, Muh. (KnE Social Sciences, 2022)
Services reach almost all aspects of human life, ranging from government services to private services such as trade, transportation services and communication services using mobile phones. The purpose of this study was to analyze the factors that affect customer satisfaction and customer loyalty. The data collection method used was a questionnaire, which was analyzed using SPSS-Amos. The results showed that service productivity affected consumer loyalty either directly or indirectly. Responsiveness only had a direct effect on customer loyalty. Accountability had an indirect effect on customer loyalty through customer satisfaction. Also, service attitude had a positive and significant effect on customer loyalty either directly or through service quality. The novelty of this study lies in the dimensions used in measuring the variables in service providers. Keywords: provider, service quality, consumer loyalty